2017
DOI: 10.29252/ijrm.15.5.287
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the factor structure, item analyses, and internal consistency of hospital anxiety and depression scale in Iranian infertile patients

Abstract: Background:The hospital anxiety and depression scale (HADS) is a common screening tool designed to measure the level of anxiety and depression in different factor structures and has been extensively used in non-psychiatric populations and individuals experiencing fertility problems. Objective: The aims of this study were to evaluate the factor structure, item analyses, and internal consistency of HADS in Iranian infertile patients. Materials and Methods: This cross-sectional study included 651 infertile patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Both subscales scores range from 0 to 21, with higher scores indicating greater levels of anxiety and depression. The Persian version of the HADS has shown satisfactory reliability and validity in infertile people [ 23 ] and has been used in many studies involving infertile people [ 3 , 24 ]. In this study, we used only the HADS-D subscale.…”
Section: Methodsmentioning
confidence: 99%
“…Both subscales scores range from 0 to 21, with higher scores indicating greater levels of anxiety and depression. The Persian version of the HADS has shown satisfactory reliability and validity in infertile people [ 23 ] and has been used in many studies involving infertile people [ 3 , 24 ]. In this study, we used only the HADS-D subscale.…”
Section: Methodsmentioning
confidence: 99%
“…Both subscales scores range from 0 to 21, with higher scores indicating greater levels of anxiety and depression. The Persian version of HADS has been validated [ 23 ] and widely used among infertile patients [ 4 , 23 ]. For this study, the Cronbach’s alpha coefficients of the HADS-A for males and females were 0.841 and 0.865, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…recent study evaluating the factor structure of the HADS in a sample of men and women at an infertility clinic concluded that a three-factor had better fit [21]. However, the above mentioned limitations, which may lead to increased risk of Type II error, may be partly outweighted by the larger statistical power due to the large sample size in the study.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…This is probably the reason why anxiety and depression detected by HADS in randomly timed health studies seem to predict clinically relevant outcomes [26,27]. Further, although a number of psychometric studies of the HADS observed a 2-factor solution with acceptable model fit for the HADS [21,28], a…”
Section: Accepted Manuscriptmentioning
confidence: 99%